Body Composition and Its Related with Hypertension in Elderly in Surakarta - Sudaryanto, Wahyu Tri; Wahyuni, Wahyuni; Herawati, Isnaini; Ayuningrum, Ika Yuli; Murti, Bhisma; Setiawan, Rizki; Putri, Nuristiqomah Dwi (RSUP Dr. Kariadi, 2023)
BACKGROUND: Several studies reported that obesity was linked to abnormal blood pressure. Obesity increases cardiovascular disease risk in adults and elderly. Body composition has been commonly measured using basic anthropometry, i.e body mass index (BMI). However, waist circumference (WC) is assumed to be more capable of capturing long-term visceral fat accumulation than BMI. Studies comparing BMI and WC to the risk of hypertension in the elderly are needed. OBJECTIVE: The aim of this study was to compare the risk of body composition using body mass index and waist circumference as risk factors for hypertension in the elderly. METHOD: A cross-sectional study was carried out in Surakarta, Central Java. A sample of 91 elderly was selected by convenience sampling. The dependent variable was hypertension. The independent variables included age, gender, body mass index (BMI), and central obesity (assessed by waist circumference). BMI and central obesity were used to measure body composition. Blood pressure was measured by a sphygmomanometer, body weight was measured by digital scale (kg), and body height was measured by stature meter (cm). Central obesity was categorized by waist circumference (WC in centimeter) measurement. The other variables were obtained from questionnaire. Comparison of body composition on hypertension were examined using simple logistic regression run on Stata 13. RESULTS: Elderly with central obesity (waist circumference ≥94 cm for males or ≥80 cm for females) had higher risk hypertension and it was statistically significant (OR= 3.07; 95% CI= 1.10 to 8.53; p= 0.032). CONCLUSION: Central obesity is significantly increase the risk hypertension in elderly.